2005
DOI: 10.1002/mar.20074
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of retail density and music tempo: Effects on shopper responses

Abstract: Research examining the effects of store environment on shoppers has found that a number of atmospheric cues have significant effects on shoppers' cognitive, affective, and behavioral responses. To date, retail atmospheric cues have been studied in isolation, instead of simultaneously, like they occur in the retail setting. This study examines the interactive effects of two atmospheric cues-retail density and music tempo-and their impact on shopper responses within a real shopping environment. Based on the sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 43 publications
7
117
0
2
Order By: Relevance
“…In conditions of high spatial density (a condition that is known to induce tension; Eroglu & Harrell, 1986), they found a positive effect of stimulus incongruency (an ambient scent associated with spaciousness decreased anxiety levels compared with an ambient scent associated with enclosed spaces); and in conditions of low spatial density, they observed a negative effect of stimulus congruency (an ambient scent associated with spaciousness significantly increased participants' anxiety levels, compared with a scent associated with physical enclosedness). Also, Eroglu, Machleit, and Chebat (2005) found that consumer evaluations of a shopping experience were highest with a moderate degree of incongruency between social density and music tempo. Like Michon et al (2005), they argued that the novelty of a moderate incongruency probably induced arousal, which mediated favorable evaluations (external perspective).…”
Section: Feelings and Behavioral Intentionsmentioning
confidence: 97%
“…In conditions of high spatial density (a condition that is known to induce tension; Eroglu & Harrell, 1986), they found a positive effect of stimulus incongruency (an ambient scent associated with spaciousness decreased anxiety levels compared with an ambient scent associated with enclosed spaces); and in conditions of low spatial density, they observed a negative effect of stimulus congruency (an ambient scent associated with spaciousness significantly increased participants' anxiety levels, compared with a scent associated with physical enclosedness). Also, Eroglu, Machleit, and Chebat (2005) found that consumer evaluations of a shopping experience were highest with a moderate degree of incongruency between social density and music tempo. Like Michon et al (2005), they argued that the novelty of a moderate incongruency probably induced arousal, which mediated favorable evaluations (external perspective).…”
Section: Feelings and Behavioral Intentionsmentioning
confidence: 97%
“…Besides, the introduction of Christmas music was found to be an effective practice that captures consumers' attention to visit their stores as music is believed to evoke the feeling of Christmas spirit and season (Spangenberg, et al, 2005). Likewise, Eroglu, Machleit and Chebat (2005) discovered that the effects of music tempo had an effect on the approach-avoidance tendency towards the store as well as the extent to which customers explore the store environment. Moreover, Yalch and Spangenberg (1988) stated that younger shoppers who were exposed to the background music tend to spend more time to shop while older shoppers showed similar tendency in the presence of foreground music.…”
Section: Musicmentioning
confidence: 99%
“…This paper aims to investigate the effect of one of the environmental cue of 3D VRR store 'Music' on virtual shoppers' behaviour. Music has been focused a lot more than any other environmental cue, in physical [2], [16], [28], [29], [45], [46], [62], [72]- [75], and web retail atmospheric [47], [53] studies. Furthermore, in this research Mehrabian and Russell's affect model [42] will be adapted to investigate the effect of background music in 3D VRR stores' on shoppers' behaviour through the mediating variables of pleasure and arousal (see Fig.…”
Section: B Virtual Reality Retailing (Vrr)mentioning
confidence: 99%